Behavioral self-regulation for weight loss in young adults: a randomized controlled trial - Wing Rena R; Gorin Amy A; Gokee-LaRose Jessica (BMC, 2009)
Abstract Objective To determine the feasibility of recruiting and retaining young adults in a brief behavioral weight loss intervention tailored for this age group, and to assess the preliminary efficacy of an intervention that emphasizes daily self-weighing within the context of a self-regulation model. Methods Forty young adults (29.1 ± 3.9 years, range 21-35, average BMI of 33.36 ± 3.4) were randomized to one of two brief behavioral weight loss interventions: behavioral self-regulation (BSR) or adapted standard behavioral treatment (SBT). Assessments were conducted at baseline, post-treatment (10 weeks), and follow-up (20 weeks). Intent to treat analyses were conducted using general linear modeling in SPSS version 14.0. Results Participants in both groups attended an average of 8.7 out of 10 group meetings, and retention rates were 93% and 88% for post-treatment and follow-up assessments, respectively. Both groups achieved significant weight losses at post-treatment (BSR = -6.4 kg (4.0); SBT = -6.2 kg (4.5) and follow-up (BSR = -6.6 kg (5.5); SBT = -5.8 kg (5.2), p < .001; but the interaction of group × time was not statistically significant, p = .84. Across groups, there was a positive association between frequency of weighing at follow-up and overall weight change at follow-up (p = .01). Daily weighing was not associated with any adverse changes in psychological symptoms. Conclusion Young adults can be recruited and retained in a behavioral weight loss program tailored to their needs, and significant weight losses can be achieved and maintained through this brief intervention. Future research on the longer-term efficacy of a self-regulation approach using daily self-weighing for weight loss in this age group is warranted. Clinical Trials Registration # NCT00488228